SISTEM INFORMASI ADMINISTRASI PADA PUSKESMAS BERBASIS MOBILE - Sidik, Muhammad; Veliyanti, Reni (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
In the current era of globalization, information technology is one of the technologies that is currently developing rapidly. Information technology has now played a very important role in the world of business or business. Besides, the presentation of a good information system is very helpful in making decisions by the management appropriately and is very helpful in improving information systems within an institution. UPTD Pegandon Public Health Center as one of the public service institutions requires the existence of an information system that is fast, accurate, effective and efficient, to improve its services to patients and the related environment in it. With such a wide scope of services, of course, there are many complex problems that occur in the service process. The number of variables also determines the speed of information flow needed by users and the Puskesmas environment. The registration process, recording payment transactions, searching for patient data and patient payment reporting systems that still use manual methods, are of course also very prone to errors. To improve patient services, it is necessary to implement an Administrative Information System and the Pegandon Public Health Center UPTD is also expected to take on a role as a facilitator in developing patient services to improve and facilitate serving and providing information through Information Technology. With the Web-Based Administrative Information System, it is hoped that the performance of the Pegandon Health Center UPTD can be improved, so that the quality and quality of service increases.